Figure replication in Soeharto Visual Meme - rizky noviasri; Yasraf Amir Piliang; Riama Maslan Sihombing (Jurnal Sosioteknologi, 2016)
Internet meme vernacularly known as  funny pictures with caption. One of them picture of Soeharto icon, smiling and waving his hand, said "piye kabare? penak jamanku, to?". Meme main principle is imitation. But imitation in Soeharto visual meme turns out in variants. It doesn't produce the same meme as its original. Mutation can be identified from the figure being used. Not all Soeharto visual meme using Soeharto icon. Using content analysis to 152 memes, this research aims to draw a replication model in Soeharto visual meme focused in figure being used. This meme replication model can be analogous as gene. But it must be distinguished between replication in meme and gene. If gene produce same transcription, than meme produce kinds of variant. Soeharto visual meme can be identified without Soeharto icon, but it should be another element which similar with its origin. If the similarity disappear than it couldn't be identified as Soeharto visual meme.